Extensive computation of albedo contrast between martian dust devil tracks and their neighboring regions - Statella, Thiago; Pina, Pedro; Silva, Erivaldo Antonio da [UNESP] (Elsevier B.V., 2015)
We have developed a method to compute the albedo contrast between dust devil tracks and their surrounding regions on Mars. It is mainly based on Mathematical Morphology operators and uses all the points of the edges of the tracks to compute the values of the albedo contrast. It permits the extraction of more accurate and complete information, when compared to traditional point sampling, not only providing better statistics but also permitting the analysis of local variations along the entirety of the tracks. This measure of contrast, based on relative quantities, is much more adequate to establish comparisons at regional scales and in multi-temporal basis using imagery acquired in rather different environmental and operational conditions. Also, the substantial increase in the details extracted may permit quantifying differential depositions of dust by computing local temporal fading of the tracks with consequences on a better estimation of the thickness of the top most layer of dust and the minimum value needed to create dust devils tracks. The developed tool is tested on 110 HiRISE images depicting regions in the Aeolis, Argyre, Eridania, Noachis and Hellas quadrangles. As a complementary evaluation, we also performed a temporal analysis of the albedo in a region of Russell crater, where high seasonal dust devil activity was already observed before, comprising the years 2007-2012. The mean albedo of the Russell crater is in this case indicative of dust devil tracks presence and, therefore, can be used to quantify dust devil activity. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Aeolian processes; Image processing; Mars, surface